Faktor-Faktor yang Mempengaruhi Pendapatan Penambang Pasir di Desa Rendang Kecamatan Rendang Kabupaten Karangasem - Rahayu, Ni Putu Dewi Agustini; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 5, Mei 2013 (pp. 226-276), 2013)
Exploitation of mineral resources or minerals such as sand is one of supporters of the construction sector, both physically, economically and socially. The need for materials such as sand mining is increasing along with the development of the construction of various facilities and physical infrastructure in various regions in Indonesia. The purpose of this study were: (1) to determine the effect of working capital, working hours, and technology simultaneously on revenue sand miners in Rendang village, (2) to determine the effect of working capital, hours worked, and technology  partially on income sand miners in Rendang village; (3) to determine differences in income sand miners in Rendang village when the use of modern technology and traditional technology. In this study the amount of sand miners were observed as many as 27 people. The data analysis technique used is the method of multiple linear regression analysis. The analysis showed that the variable capital, working hours, and technology simultaneously significant effect on earnings sand miners in Rendang village. Variable capital and working hours in partial positive and significant effect on earnings sand miners in Rendang village, and sand miners income in Rendang village using modern technology is higher than using traditional technologies.
Keywords: working capital; hours of work; technology; sand miners; revenue